Management of Epstein–Barr virus-related post-transplant lymphoproliferative disorder after allogeneic hematopoietic stem cell transplantation - Liu, Li (Ther Adv Hematol, 2020)
Epstein–Barr virus-related post-transplant lymphoproliferative disorder (EBV-PTLD) is a rare but life-threatening complication after allogeneic hematopoietic stem cell transplantation (allo-HSCT). T-cell immunodeficiency after transplantation and EBV primary infection/reactivation play major roles in the pathogenesis. Unspecific clinical manifestations make the diagnosis difficult and time consuming. Moreover, this fatal disease usually progresses rapidly, and leads to multiple organ dysfunction or death if not treated promptly. Early diagnosis of EBV-DNAemia or EBV-PTLD generally increases the chances of successful treatment by focusing on regular monitoring of EBV-DNA and detection of symptomatic patients as early as possible. Rituximab ± reduction of immunosuppression (RI) is currently the first-line choice in preemptive intervention and targeted treatment. Unless patients are suffering from severe graft versus host disease (GvHD), it is better to combine rituximab with RI. Once a probable diagnosis is made, the first-line treatment should be initiated rapidly, along with, or ahead of, biopsy, although histopathologic confirmation is requisite. In addition, EBV-specific cytotoxic T lymphocytes (EBV-CTLs) or donor lymphocyte infusion (DLI) has shown promise in cases of suboptimal response. Chemotherapy ± rituximab might lend more opportunities to refractory/relapsed patients, who might also benefit from ongoing clinical trials. Herein, we discuss our clinical experience in detail based on the current literature and our five cases.